สมรรถนะผู้ประกอบการการค้าชายแดนไทย-มาเลเซียเพื่อรองรับประชาคมเศรษฐกิจอาเซียน - เอมเอก, นวิทย์; ใจแก้ว, อาคม; แก้วจานงค์, อนิวัช (Thai Interdisciplinary and Sustainability Review, 2019)
This article is a documentary research by using secondary data. The purpose of this research is to study the correlation structure of the causal factors that competencies required for Thai-Malaysia border trade entrepreneurs to support the ASEAN Economic Community. The objective of this study was to investigate the competencies needed for the trade along the Thai-Malaysian to support the ASEAN Economic Community. To analyze Entrepreneurship factor, Leadership skill factor, Core Management competency skill factor, Management skills of entrepreneurs factor, AEC Blueprint, and Southern Province Development Plan (2010-2013) (Revised version 2011). For develop Thai-Malaysia border trade Entrepreneurs Competency Framework to support trade liberalization within ASEAN properly.